Prevalence of risk factors for primary postpartum hemorrhage in a university hospital - Thaís Betti; Helga Geremias Gouveia; Vanessa Aparecida Gasparin; Letícia Becker Vieira; Juliana Karine Rodrigues Strada; Júlia Fagherazzi (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to identify the risk factors associated with primary postpartum hemorrhage in a university hospital. Methods: a cross-sectional study was conducted with 277 postpartum women who received care during childbirth or cesarean section between June and August 2020. Data were collected using a pre-structured questionnaire administered 24 hours after delivery. Poisson Regression was employed to analyze the factors associated with postpartum hemorrhage. Results: postpartum hemorrhage was observed in 30% of the study sample. Shock Index and uterine distension were found to be statistically associated with postpartum hemorrhage. Postpartum women with a Shock Index ≥ 0.9 had a 61% higher prevalence of postpartum hemorrhage (PR=1.61, 95% CI: 1.07 - 2.43), while those with uterine distension had a 134% higher prevalence (PR=2.34, 95% CI: 1.63 - 3.36). Conclusions: recognizing these factors contributes to improvements in clinical practice, as they enable the prediction of their occurrence and call for appropriate management, thereby preventing unfavorable outcomes.